The criminalization of Senegalese in the city of Buenos Aires, in the period 2015-2019.: An approach from the intersectionality - Rabasa, Jeremías Pérez (Faculdade de Ciências e Letras - Unesp - Araraquara., 2021)
This paper is an analysis of Senegalese migration in the Autonomous City of Buenos Aires. The particular interest of this study is the criminalization to which they were subjected with the inauguration of the liberal-conservative government of Alianza Cambiemos. It is pointed out that the criminalization of this group is the intersection of erent discriminations to which they are subjected by the State, the most important factors being regulatory changes in immigration matters, street persecution by the security forces, violence against them in the approach and the applied judicial regulations, promoted by multinationals. These presented reflections are a partial result of an investigation carried out by this author within the framework of a PhD scholarship.